FGF signaling refines Wnt gradients to regulate the patterning of taste papillae - Prochazkova, Michaela; Häkkinen, Teemu J; Prochazka, Jan; Spoutil, Frantisek; Jheon, Andrew H; Ahn, Youngwook; Krumlauf, Robb; Jernvall, Jukka; Klein, Ophir D (Development, 2017)
The patterning of repeated structures is a major theme in developmental biology, and the inter-relationship between spacing and size of such structures is an unresolved issue. Fungiform papillae are repeated epithelial structures that house taste buds on the anterior tongue. Here, we report that FGF signaling is a crucial regulator of fungiform papillae development. We found that mesenchymal FGF10 controls the size of the papillary area, while overall patterning remains unchanged. Our results show that FGF signaling negatively affects the extent of canonical Wnt signaling, which is the main activation pathway during fungiform papillae development; however, this effect does not occur at the level of gene transcription. Rather, our experimental data, together with computational modeling, indicate that FGF10 modulates the range of Wnt effects, likely via induction of Sostdc1 expression. We suggest that modification of the reach of Wnt signaling could be due to local changes in morphogen diffusion, representing a novel mechanism in this tissue context, and we propose that this phenomenon might be involved in a broader array of mammalian developmental processes.
Keywords: Animals; myši transgenní; biologické modely; Female; chuťové pohárky; počítačová simulace; Mice, Transgenic; ženské pohlaví; Mice, Knockout; myši knockoutované; Hedgehog Proteins; kostní morfogenetické proteiny; Models, Biological; Mice; těhotenství; intracelulární signální peptidy a proteiny; membránové proteiny; Fibroblast Growth Factor 10; myši; Body Patterning; Wnt Signaling Pathway; Computer Simulation; Taste Buds; Bone Morphogenetic Proteins; Male; signální dráha Wnt; Intracellular Signaling Peptides and Proteins; Membrane Proteins; zvířata; mužské pohlaví; Pregnancy; proteiny hedgehog; fibroblastový růstový faktor 10; rozvržení tělního plánu